An overview of energy savings potentials through mobile forwarding proxy framework. (23rd September 2014) - Seeling, Patrick
Increasingly, mobile users interact with more than their primary mobile device, a trend that will likely continue with the growth of the internet of things. We introduce an application data forwarding framework, which is based on a mobile user's primary device and geared towards energy savings for the multitude of devices a mobile user interacts with. Based on the need to have a recent copy of application data available on a mobile user's primary device, e.g., a smartphone, our framework forwards, e.g., Facebook status updates, to external devices in vicinity. We provide an evaluation of the energy consumption and potentials for savings using our proposed approach by means of cost–based evaluations. Assuming that external devices could derive the data through cellular or wireless LAN connections as alternatives, we find that significant savings for the group of devices could be realised. Specifically, for an active social network account with frequent updates, we find that the external devices would be able to conserve power, while the additional burden on the primary device's battery remains reasonably low.